Imports, Exports and Domestic Innovation - Dominik Boddin (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
By crawling online data, I create a new long-term patenting panel dataset for Germany to identify the causal effect of trade integration with Eastern Europe and China on patenting in the period 1993-2012. I exploit the cross-regional variation in the German industry structure and use trade flows to other advanced economies as instruments for regional import and export exposure. I find that an increase in the net trade exposure (defined as import- minus export exposure) causes an increase in regional patenting. This effect is purely driven by a positive link between import exposure and innovation, whereas export exposure does not influence innovation. Interestingly, the effects are heterogeneous across exposure origin. The positive link between import exposure and innovation is fully explained by trade integration with Eastern Europe. Increasing integration with China has no effects on innovation.
Keywords: F14; O30; R11; R12; 330